An integrated experimental and economic evaluation of cell therapy affinity purification technologies. (June 2017) - Weil, Benjamin D; Jenkins, Michael J; Uddin, Siddique; Bracewell, Daniel G; Wellings, Donald; Farid, Suzanne S; Veraitch, Farlan
Aim: To present an integrated techno-economic analysis assessing the feasibility of affinity purification technologies using the manufacture of induced pluripotent stem cell-derived progenitor photoreceptors for retinal dystrophies as a case study.Materials & methods: Sort purity, progenitor yield and viable cell recovery were investigated for three cell sorting techniques: fluorescent-activated cell sorting (FACS); magnetic-activated cell sorting (MACS); and a novel technology SpheriTech beads. Experimentally derived metrics were incorporated into an advanced bioprocess economics tool to determine cost of goods per dose for each technology.Results & conclusion: Technical and bioprocess benefits were noted with SpheriTech beads which, unlike FACS and MACS, require no cell labeling. This simplifies the bioprocess, reduces cell loss and leaves target cells label free. The economic tool predicted cost drivers and a critical dose (7 × 10 7 cells per dose) shifting the most cost-effective technology from FACS to MACS. Process optimization is required for SpheriTech to compete economically.